Practical use of a multicenter clinical research support system connected to electronic medical records. (October 2021) - Manabe, Shirou; Takeda, Toshihiro; Hattori, Atsushi; Yamamoto, Masashi; Shimai, Yoshie; Namiuchi, Yoshiki; Yamaguchi, Junji; Yamada, Tomomi; Konishi, Shozo; Matsumura, Yasushi
Highlights: We constructed a network system that supports multicenter collaborative clinical studies linked with the electronic medical records of five companies. The data of observational studies can be collected from 19 hospitals, centering on Osaka University Hospital. A medical image collection system was introduced. We have supported 28 clinical studies and collected data on 9987 cases over 7 years. Abstract: Background: Electronic medical records (EMRs) are widely used, but in many cases, they are used within a network physically separated from the Internet. Multicenter clinical studies use Internet-connected electronic data capture (EDC) systems to collect data, where data entered into the EMR are manually transcribed into the EDC system. In addition, medical images for clinical research are also collected manually. Variations in EMRs and differing data structures among vendors hamper the use of data for clinical research. Methods: We solved this problem by developing a network infrastructure for clinical research between Osaka University Hospital and affiliated hospitals in the Osaka area and introducing a clinical data collection system (CDCS). In each hospital's EMR network, we implemented a CRF reporter that accumulated data for clinical research using a template and then sent the data to a management server in the Osaka University Hospital Data Center. To organize the patient profile data and clinical laboratory data stored in each EMR for use in clinical research, the data are retrieved from the template by an interface module developed by each vendor, according to our common data output interface specification. The data entered into the CRF reporter template for clinical research are also recorded in the EMR progress notes and sent to the data management server. This network infrastructure can also be used as a medical image collection system that automatically collects images for research from PACS at each hospital. These systems are managed under common subject numbers issued by the CDCS. Results: A network infrastructure was established among 19 hospitals, and a CRF reporter was incorporated into the EMR. A medical image transfer system was introduced in 13 hospitals. Since 2013, 28 clinical studies have been conducted using this system, and data for 9, 987 cases have been collected as of December 31, 2020. Conclusion: Incorporating a CRF reporter with medical image transfer system into the EMR has proven useful for collecting research data.